Analysis of Adolescent Fertility Aged 10-14 Calculation Results in Indonesia - Ari Purbowati; Yogo Aryo Jatmiko; Ikhsan Fahmi (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2019)
The adolescent's fertility aged 10-14 years is one of the national and international focus of attention as outlined in Sustainable Development in 2030 target 3.7. To fulfill these targets, there is 3.7.2 indicator regarding adolescent fertility (10-14 and 15-19 years). The indicator that was used to measure adolescent fertility is the Age-Specific Fertility Rate (ASFR). The availability of information about this indicator can help the stakeholders to understand their current situations and their needs in order to prepare for healthier adolescence and adulthood. So far, there is not much information about ASFR 10-14. Usually, ASFR is calculated for aged 15-49 years. It is because of adolescent fertility aged 10-14 are very rare cases and the data sources that can be used to calculate them are limited. The aim of this study is to calculate ASFR aged 10-14 years in Indonesia use the 2012 IDHS, 2015 inter-census population survey, and the 2017 IDHS data. The methods used are direct method, a direct method with modification, and Schmertmann method. Based on calculations from three methods, it can be concluded that ASFR aged 10-14 years in Indonesia is still very low (under 1 per 1000 births). That can be interpreted that not many birth cases are found for women aged 10-14 years in Indonesia.